Case Report: Convalescent Plasma Achieves SARS-CoV-2 Viral Clearance in a Patient With Persistently High Viral Replication Over 8 Weeks Due to Severe Combined Immunodeficiency (SCID) and Graft Failure - Keitel, Verena; Bode, Johannes Georg; Feldt, Torsten; Walker, Andreas; Müller, Lisa; Kunstein, Anselm; Klindt, Caroline; Killer, Alexander; Senff, Tina; Timm, Jörg; Ostermann, Philipp; Damagnez, Maximilian; et al. (Frontiers in Immunology, 2021)
We describe the unique disease course and cure of SARS-CoV-2 infection in a patient with SCID and graft failure. In absence of a humoral immune response, viral clearance was only achieved after transfusion of convalescent plasma. This observation underscores the necessity of the humoral immune response for SARS-CoV-2 clearance.